Errors linked to medication management in nursing homes: an interview study - Mariette Bengtsson; Ann-Britt Ivarsson Ekedahl; Karin Sjöström (BMC, 2021)
Abstract Background The number of errors in medication management in nursing homes is increasing, which may lead to potentially life-threatening harm. Few studies on this subject are found in the municipal nursing home setting, and causes need to be identified. The aim of this study was to explore perceptions of errors connected to medication management in nursing homes by exploring the perspective of first-line registered nurses, registered nurses, and non-licensed staff involved in the care of older persons. Methods A qualitative research approach was applied based on semi-structured interviews with 21 participants at their workplaces: Seven in each of the occupational categories of first-line registered nurses, registered nurses, and non-licensed staff. Subcategories were derived from transcribed interviews by content analysis and categorized according to the Man, Technology, and Organization concept of error causation, which is as a framework to identify errors. Results Mistakes in medication management were commonly perceived as a result of human shortcomings and deficiencies in working conditions such as the lack of safe tools to facilitate and secure medication management. The delegation of drug administration to non-licensed staff, the abandonment of routines, carelessness, a lack of knowledge, inadequate verbal communication between colleagues, and a lack of understanding of the difficulties involved in handling the drugs were all considered as risk areas for errors. Organizational hazards were related to the ability to control the delegation, the standard of education, and safety awareness among staff members. Safety issues relating to technology involved devices for handling prescription cards and when staff were not included in the development process of new technological aids. A lack of staff and the lack of time to act safely in the care of the elderly were also perceived as safety hazards, particularly with the non-licensed staff working in nursing homes. Conclusions The staff working in nursing homes perceive that the risks due to medication management are mainly caused by human limitations or technical deficiencies. Organizational factors, such as working conditions, can often facilitate the occurrence of malpractice. To minimize mistakes, care managers need to have a systemwide perspective on safety issues, where organizational issues are essential.